Study on the professional education of urban and rural planning: Based on the perspective of modern discipline development - WANGJiwu(王纪武); ZHANGNiansi(张念思); GUYichuan(顾怡川) (Zhejiang da xue xue bao. Journal of Zhejiang University. Sciences edition. Li xue ban, 2016)
By the theories of philosophy science, analyses have been done on the problems of professional identity crisis and subject identity debate in urban[whitesquare]rural planning fields. It indicates that the establishment of urban and rural planning discipline is a historical progress through deviating from the previous framework of material planning. Deep mechanism is the transformation from modern subject to postmodern subject. According to the analysis of the concept and the trend of modern science development, this paper presents the knowledge production mode of urban[whitesquare]rural planning discipline should be based on the team work of different scientific communities. Professional education should adhere to the space trait and transform the education form from elite education which is small and complete to large and special education. In this way, development form of urban and rural society can be switched from leading by separated elite to cooperation of different scientific communities.